SOSIALISASI PEMBUATAN BODY MIST EKSTRAK MELON (Curcumis melo L) SEBAGAI ANTIOKSIDAN DI SMAN PASUNDAN 1 CIMAHI - Erika Cantika; Rizky Permana; Cindy Putri Apriliani; Erliyana Herawati Guslimar; Ayu Winda Nurfauziyah; Tanti Jumianti; Raffles Yoandri Naskata; Sharen Rizky Adriana (Jurnal Pengabdian IKIFA, 2024)
Introduction Free radicals originate from metabolic processes within the body (endogenous), such as protein, carbohydrates, and fats in mitochondria, inflammation or inflammatory processes, iron-mediated reactions, etc. Additionally, free radicals can originate from outside the body (exogenous), for example, from cigarette smoke, pollution, radiation, UV rays, drugs, pesticides, industrial waste, and ozone. Melon contains a significant amount of vitamin C. Vitamin C in melon fruit serves as an antioxidant. Antioxidant compounds are used as a defense against free radicals that damage skin tissue. Objective information to the younger generation about the utilization of natural plant materials, one of which is melon fruit (Cucumis melo L), which can be made into extracts for body mist products as antioxidants. The method in community service involves socializing the production process. The result of this community service is that by socializing, there is a great opportunity to increase information and insight among the younger generation regarding the significant potential of easily obtainable plants in Indonesia.